ROLE OF SOCIAL MEDIA INFLUENCERS IN PROMOTING SUSTAINABLE PRODUCTS AND PRACTICES AND THEIR POTENTIAL TO DRIVE POSITIVE CHANGE - Dr. Pooja Sharma; Dr. Darshan Subherwal (Galaxy International Interdisciplinary Research Journal, 2024)
Social media influencers have emerged as powerful agents of change, influencing consumer behaviors and attitudes towards sustainability. This comprehensive literature review examines the evolving role of social media influencers in promoting sustainability and driving positive change. Drawing from a wide range of studies, the review explores the effectiveness of influencer marketing strategies, the impact of authenticity and credibility, and the potential challenges and ethical considerations associated with sustainability-focused influencer campaigns. The findings highlight the significant potential of social media influencers in accelerating the adoption of sustainable practices and products, while also identifying areas for future research.